2016
DOI: 10.1017/s0950268815003143
|View full text |Cite
|
Sign up to set email alerts
|

Prospective clinical and serological follow-up in early childhood reveals a high rate of subclinical RSV infection and a relatively high reinfection rate within the first 3 years of life

Abstract: Children encounter repeated respiratory tract infections during their early life. We conducted a prospective clinical and serological follow-up study to estimate the respiratory syncytial virus (RSV) primary infection and reinfection rates in early childhood. Sera were collected from 291 healthy children at the ages of 13, 24 and 36 months and antibody levels against RSV antigens were determined by enzyme immunoassay. The RT-PCR method was also used for identifying the possible presence of RSV in symptomatic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 28 publications
4
42
0
Order By: Relevance
“…The quick rise in the percentage seropositive observed in our data is indicative of a high rate of infection in the present population. High rates of infection, attributed to frequent reinfections, have also been observed in other studies [3032], implying that the results from our analysis could be generalized to other settings.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The quick rise in the percentage seropositive observed in our data is indicative of a high rate of infection in the present population. High rates of infection, attributed to frequent reinfections, have also been observed in other studies [3032], implying that the results from our analysis could be generalized to other settings.…”
Section: Discussionsupporting
confidence: 85%
“…An estimate of 0.0/person/year for the force of infection acting on children who still have maternally acquired antibodies is in line with studies that show that the infant IgG response following primary infection is very low [15, 16, 32], and in fact, Ochola et al [16] showed that the pristine rate of decay of maternal antibodies was not different from the rate of decay including the infants who had had an RSV infection. Estimating our model parameters while excluding the LRTI positive sample and the RSV positive samples gave pristine maternal antibody decay rates of 2.56/year and 2.45/year, not very different from 2.54/year obtained with the entire data set.…”
Section: Discussionsupporting
confidence: 73%
“…The levels of anti -F IgG in acute phase were significantly higher in children aged at 19 to 36 months old than those at 13 to 18 months old, and the levels of IgG1 and IgG2 for F protein in the convalescent phase were higher in children 19 months and older than in children < 19 months old [mean values of IgG1: 472 (19–36 mo) versus 118 (13–18 mo), p  < 0.0001, that of IgG2: 6.63 (19–36 mo) versus 0.70 (13–18 mo), p  < 0.0001], suggesting that repetitive RSV infections boost the responses of IgG1 and IgG2 to F protein. Recent epidemiological surveillance data suggested that the annual RSV circulation boosts basic immune responses against RSV especially in healthy children aged 2 years and older and healthy adults, resulting in few symptomatic RSV patients in such population (Kutsaya et al, 2016). With regard to GMRs C/A of F IgGtotal, IgG1, and IgG2, the lower limits of 95% CI were > 58, 48, and 5.3 in infants at 7 to 12 months old, > 255, 227, and 12 in children at 13 to 18 months old, > 23, 22, and 11 in children at 19 to 36 months old, and > 5.0, 4.7, and 3.9 in adults (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Repeated RSV infections have been documented for both children and adults. It is estimated that more than 30% of children have RSV reinfections during 3 years of follow‐up . Respiratory syncytial virus reinfection in healthy adults is considered common, with most being asymptomatic or presenting with mild upper respiratory tract symptoms .…”
Section: Epidemiology and Clinical Featuresmentioning
confidence: 99%
“…It is estimated that more than 30% of children have RSV reinfections during 3 years of follow-up. 46 Respiratory syncytial virus reinfection in healthy adults is considered common, with most being asymptomatic or presenting with mild upper respiratory tract symptoms. 47,48 The host immune status and the current circulating RSV strains are thought to be factors that influence reinfections, with natural infections generating incomplete and insufficient immunity.…”
Section: Epidemiology and Clinical Featuresmentioning
confidence: 99%